To confirm the existence of Black hole cosmology - UV, Satya Seshavatharam; S, Lakshminarayana (International Journal of Advanced Astronomy, 2013)
It may be noted that, increased redshifts and increased distances forced Edwin Hubble to propose the Hubble’s law. In fact there is no chance or scope or place for 'galaxy receding'. If it is possible to show that, (from the observer) older galaxy’s distance increases with its ‘age’, then automatically the concepts  ‘galaxy receding’ and ‘accelerating universe’ can be put for a revision at fundamental level. Its only our belief in its 'given' (Doppler shift based) unproven cosmological interpretation. Even then, merely by estimating galaxy distance  and without measuring galaxy receding speed, one cannot verify its acceleration.  Clearly speaking: two mistakes are happening here. 1) Assumed galaxy receding speed  is not being measured and not being confirmed. 2) Without measuring and confirming the galaxy receding speed, how can one say and confirm that  it (galaxy)  is accelerating.  It is really speculative and unfortunate also. During cosmic expansion, assuming past and present galaxies (which actually found to have gigantic structures) as ‘points’  and guessing photons coming from that  galactic point particles  seem to be ad-hoc. If light is coming from the atomic matter of the gigantic galaxy, then cosmic redshift can be interpreted as an index of the galactic atomic ‘light emission mechanism’. In no way it seems to be connected with ‘galaxy receding’.  Whatever may be the expression, definitions of cosmic red shift seem to be  ad-hoc and not absolute. Hence with redshift concept - one may not be able to understand the actual rate of cosmic expansion and actual cosmic geometry.  Some cosmologists use the term ‘Hubble volume’ to refer to the volume of the observable universe.  At any given time, the product of ‘critical density’ and ‘Hubble volume’ gives a characteristic cosmic mass and it can be called as the ‘Hubble mass’. Interesting thing is that, Schwarzschild radius of the Hubble mass again matches with the Hubble length. Most of the cosmologists believe that this is merely  a coincidence. If one is able to show its applications in different areas of fundamental physics, certainly it can be given more significance and superiority compared to the mysterious ‘dark energy’. At any given cosmic time, ‘Hubble length’ can be considered as the gravitational or electromagnetic interaction range. Hubble volume and Hubble mass play a crucial role in quantum physics, nuclear physics, atomic physics and particle physics. If universe constitutes so many galaxies, if each galaxy constitutes a central fast growing and (light speed) spinning black hole and if black hole geometry is more intrinsic than its ‘mass’ and ‘mass density’, then considering universe as a ‘growing and light speed rotating black hole’ may not be far away from reality. Unknowingly the fundamental physical laws are being developed, being executed and being proven inside and under the background of a growing and light speed rotating black hole universe. It can be suggested that, ‘quantum of angular momentum’ may be due to the cosmological manifestation and ‘discrete nature’ of angular momentum may be due the discrete nuclear matter. In any bound system, ‘operating force’ only plays major role in maintaining the ‘existence of the bound system’ and ‘angular momentum’ is one of the result. If one is able to make the operating force as discrete, then automatically one can observe a discrete structure like discrete radii, discrete angular momentum and discrete energy levels. Alternatively if atomic nucleus constitutes any fixed number of protons and any fixed number of neutrons, it is possible to guess  that- nuclear mass is discrete. If nuclear matter is discrete, it is also possible  to have a discrete  atomic structure . In this new direction authors noticed some interesting and very strange coincidences.  Main problem is that, the new relations are very simple to understand and very difficult  to confirm. The most important point to be noted here is that, synthesis of elementary physical constants seem to be more fundamental than the ‘cosmological  nucleosynthesis’.